Tomato Fruit Borer (Neoleucinodes elegantalis) in Tomate in Loma Bonita, Oaxaca, Mexico - Palacios Torres, Rogelio Enrique; Antonio Luis, María del Carmen; Castañeda Vildózola, Álvaro; Hernández Hernández, Hipólito; Solís, M. Alma (The Southwestern Entomologist, 2024)
Neoleucinodes elegantalis (Guenée), the tomato fruit borer, is reported from Oaxaca, Mexico.
Keywords: Tomate; Loma Bonita; Neoleucinodes elegantalis (Guenée)